Nesting ecology of Megachile (Sayapis) mendozana Cockerell and its synonymy with Megachile (Sayapis) santiaguensis Durante (Hymenoptera: Megachilidae) - Torretta, Juan Pablo (2011)
We synonymized M. santiaguensis Durante with M. mendozana Cockerell based on individual siblings of different sex obtained from a trap-nest. Similarity in morphology between individuals of both sexes of M. mendozana, as well as the overlapping distribution, provides further evidence to support this synonymy. Also, we report aspects of nesting ecology and analyze the pollen in cell provisions and/or feces of 11 samples of 4 different trap-nests. Additionally, floral host, associated organisms, and new geographical records are provided.